Stability Analysis of Bipolar LVDC Grid - T. Raghu; D. Rajesh Reddy (International Transactions on Electrical Engineering and Computer Science, 2022)
The study and regulation of bipolar DC structures covered by asymmetrical action, the DC symmetric part approach is implemented. This approach is an expansion of the standard principle of symmetrical components in three phase AC-controlled networks. In typical and differential modes, the asymmetrical voltage and current in the positive and negative poles are separated into symmetric segments. For each mode, an analogous circuit is imitative, which produces decoupled case circuits. As a consequence, it provides autonomous recommendations of each situation and offers an informative mode of a bipolar DC power system’s static and dynamic behavior. A common methodology which is relevant to numerous cases of device scheme is the DC symmetrical portion process. An improved common-mode voltage control scheme is defined as an example. By incorporating active damping regulation, it suppresses common mode LC resonance and decreases common-mode impedance to enhance power efficiency and stability of voltage. Matlab/Simulink effects validate the main theoretical assumptions.